Monitoring and Managing Land Use Methodology: Understanding the interactions between Nature / Society for land use management in rural areas - Lourenço, Nelson (2012)
Understand the meanings and motives underneath the processes of land use / land cover changes is an important issue to the knowledge of these processes of change. In this way the scientific basis of this work is the belief that integrating physical and socio-economic approaches in the study of land resources and land use systems represents a conceptually correct means of addressing the unifying issue of economic and environmental sustainability.